Determination of a Suicide with of Hydrogen Sulfide on a Putrefied Corpse - Özdemirel, Rifat Özgür; Kömür, İlhami; Başpınar, Bünyamin; Demir, Muhammet; Yılmaz, Süleyman (The Bulletin of Legal Medicine, 2016)
H2S poisoning is found rarely. It’s often encountered in industrial accidents and in the sewage works. Deaths due to H2S poisoning occur as a result of inhalation. When the level of the H2S in ambient air is higher than 500 ppm, death occurs within minutes.Our case was a 23-year-old man, who was found dead at home with putrefaction findings. In our case, metabolites of hemoglobin were found in the first toxicological analysis. It is thought that these metabolites may occur due to putrefaction, so a certain comment has not been made about the cause of death. Detection of sulfur in the bottles at the scene and written notes was hung outside the door of the house which includes “Attention!, H2S is very toxic, take notes, get out, close the door” suggested that death outcomes from H2S poisoning.In cases which suspected poisoning and signs of putrefaction has begun, detailed crime scene investigation often be ahead of postmortem examination and toxicological analysis while determining the cause of death.Keywords: Hydrogen sulfur, Suicide, Death, Autopsy.
Keywords: hydrogen sulfur; suicide; death; autopsy